Pengujian Determinan Penggelapan Pajak - S Suyanto; Tri Astuti (Akademi Akuntansi YKPN Yogyakarta, 2023)
The goal of this study was to determine how tax penalties, tax processes, tax technologies, and the love of money affected case studies of tax cheating involving taxpayers in the Kulon Progo Regency. This form of research uses a questionnaire to gather data and takes a quantitative approach. Purposive sampling of respondents was used in this study. Multiple linear regression was the method employed in this study's data analysis. The findings of this study demonstrate that taxationsu technology reduces tax avoidance. Tax penalties, the tax code, and the love of money, on the other hand, have a negative impact on tax evasion.